Effects of three different water temperatures on dehydration in competitive swimmers - Macaluso, F.; Di Felice, V.; Boscaino, G.; Bonsignore, G.; Stampone, T.; Farina, F.; Morici, G. (Science & Sports, 2011)
Aims: The purpose of this study was to evaluate the effects of three different water temperatures on physiological responses (dehydration, sweat rate, urine output, rectal temperature and plasma electrolytes) of competitive athletes during a "simulated" race of 5 km in an indoor swimming pool. Methods: Nine male competitive master swimmers swam 5 km with the water at temperatures of 23, 27 and 32°C. Immediately before (Pre) and after (Post) each trial, samples of blood and urine were collected, body weight was recorded and rectal temperature was measured. The dehydration percentage and sweat rate were the highest at 32°C and the lowest at 23°C (23°C: -0.9 ± 0.5; 27°C: -1.3 ± 0.6; 32°C: -2.2 ± 0.7% and 23°C: 0.48 ± 0.28; 27°C: 0.76 ± 0.36; 32°C: 1.25 ± 0.37 l/h). The Post urine volume output was not significantly different in the three trials (23°C: 122.6 ± 62.4; 27°C: 78.2 ± 24.9; 32°C 81.4 ± 37.0 mL). The 27 and 32°C water increased the rectal temperature (Pre: 37.0 ± 0.3; Post: 37.9 ± 0.5°C-Pre: 36.9 ± 0.4; Post: 38.0 ± 0.4°C, respectively). Results: This study shows that dehydration, sweat rate and body temperatures simultaneously increase with the rise of water temperature during the shortest open water swimming event distance (5 km) performed at race intensity.